2013
DOI: 10.18632/aging.100587
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic and space radiation exposure of mouse brain causes impaired DNA repair response and premature senescence by chronic oxidant production

Abstract: Despite recent epidemiological evidences linking radiation exposure and a number of human ailments including cancer, mechanistic understanding of how radiation inflicts long-term changes in cerebral cortex, which regulates important neuronal functions, remains obscure. The current study dissects molecular events relevant to pathology in cerebral cortex of 6 to 8 weeks old female C57BL/6J mice two and twelve months after exposure to a γ radiation dose (2 Gy) commonly employed in fractionated radiotherapy. For a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 76 publications
5
46
0
Order By: Relevance
“…Most importantly, the early BBB opening in the female hippocampus was correlated with the delayed and late-delayed memory function declines. The greater sensitivity to radiation-induced neurocognitive declines in the elderly females is supported by the biological findings of radiation-caused aging-like pathology 26 .…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Most importantly, the early BBB opening in the female hippocampus was correlated with the delayed and late-delayed memory function declines. The greater sensitivity to radiation-induced neurocognitive declines in the elderly females is supported by the biological findings of radiation-caused aging-like pathology 26 .…”
Section: Discussionmentioning
confidence: 81%
“…Although the exact mechanism of the age-dependent radiosensitivity remained unknown, previous studies 24, 25 have shown that RT has more adverse effects on older patients. Moreover, the radiation-induced aging-like pathology in cerebrocortical cells has been suggested 26 , including shrinkage of cortical thickness, activation of cell-cycle arrest pathway and inhibition of DNA double strand break repair. Also, it has been shown that exposing cerebral cortex to radiation increases chronic oxidative stress, oxidant DNA damage, lipid peroxidation, and apoptosis 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baluchamy et al (2012Baluchamy et al ( , 2010 and Suman et al (2013) demonstrated induction of lipid peroxidation and ROS in mouse brains accompanied by reduced levels of glutathione and superoxide dismutase activity following γ-ray, 1 H, and 56 Fe ion exposures. In mice, persistent oxidative changes are induced by <1 Gy of charged particles.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…In light of these data, nestin may have a role in acquiring resistance to radiation therapy. Nestin has also been reported to be expressed increasingly after radiation injury to the brain (26), although the precise mechanism of this finding was not identified. This observation may indicate an important role of nestin in the response to cellular injury by irradiation therapy.…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 99%